A calculus problem by Akshat Sharda

Calculus Level 5

d x ( x 2 + 2 x + 2 ) x 2 + 2 x + 4 \int \dfrac{dx}{(x^2+2x+2)\sqrt{x^2+2x+4}}

Find the above integral.

Notation: C C in the answer options denotes the constant of integration .

None of these. 1 2 tan 1 ( 1 x + 1 x 2 + 2 x + 2 2 ) + C \frac{1}{\sqrt{2}} \tan^{-1}\left(\frac{1}{x+1} \sqrt{\frac{x^2+2x+2}{2}}\right) + C 1 2 tan 1 ( 1 x + 1 x 2 + 2 x + 4 2 ) + C -\frac{1}{\sqrt{2}} \tan^{-1}\left(\frac{1}{x+1} \sqrt{\frac{x^2+2x+4}{2}}\right) + C 1 2 tan 1 ( 1 x + 2 x 2 + 2 x + 4 4 ) + C -\frac{1}{\sqrt{2}} \tan^{-1}\left(\frac{1}{x+2} \sqrt{\frac{x^2+2x+4}{4}}\right) + C 1 2 tan 1 ( 1 x + 4 x 2 + 2 x + 4 2 ) + C \frac{1}{\sqrt{2}} \tan^{-1}\left(\frac{1}{x+4} \sqrt{\frac{x^2+2x+4}{2}}\right) + C

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

d x ( ( x + 1 ) 2 + 1 ) ( x + 1 ) 2 + 3 \large \displaystyle \int _{ }^{ }\frac{dx}{\left(\left(x+1\right)^2+1\right)\sqrt{\left(x+1\right)^2+3}}

Let x + 1 = 3 tan t d x = 3 sec 2 t d t \large \displaystyle x+1 = \sqrt{3}\tan t \implies dx = \sqrt{3}\sec ^2t\ dt

3 sec 2 t d t ( 3 tan 2 t + 1 ) 3 sec t = sec t d t 3 tan 2 t + 1 \large \displaystyle \int _{ }^{ }\frac{\sqrt{3}\sec ^2t\ dt}{\left(3\tan ^2t+1\right)\sqrt{3}\sec t} = \int _{ }^{ }\frac{\sec tdt}{3\tan ^2t+1}

Multiplying top and bottom by cos 2 t \large \displaystyle \cos ^2t ,

cos t d t 3 sin 2 t + cos 2 t = cos t d t 3 sin 2 t + 1 sin 2 t = cos t d t 2 sin 2 t + 1 \large \displaystyle \int _{ }^{ }\frac{\cos tdt}{3\sin ^2t+\cos ^2t} = \int _{ }^{ }\frac{\cos tdt}{3\sin ^2t+1-\sin ^2t} = \int _{ }^{ }\frac{\cos tdt}{2\sin ^2t+1}

Let u = sin t d u = cos t d t \large \displaystyle u = \sin t \implies du = \cos t\ dt . hence,

= d u 2 u 2 + 1 = d u ( 2 u ) 2 + 1 = 1 2 tan 1 ( 2 u ) + C \large \displaystyle =\int _{ }^{ }\frac{du}{2u^2+1} = \int _{ }^{ }\frac{du}{\left(\sqrt{2}u\right)^2+1} = \frac{1}{\sqrt{2}}\tan ^{-1}\left(\sqrt{2}u\right)+C

= 1 2 tan 1 ( 2 sin t ) + C \large \displaystyle = \frac{1}{\sqrt{2}}\tan ^{-1}\left(\sqrt{2}\sin t\right)+C

= 1 2 tan 1 ( 2 ( x + 1 ) x 2 + 2 x + 4 ) + C \large \displaystyle = \frac{1}{\sqrt{2}}\tan ^{-1}\left(\frac{\sqrt{2}\left(x+1\right)}{\sqrt{x^2+2x+4}}\right)+C

= 1 2 ( π 2 cot 1 ( 2 ( x + 1 ) x 2 + 2 x + 4 ) ) + C \large \displaystyle = \frac{1}{\sqrt{2}}\left(\frac{\pi }{2}-\cot ^{-1}\left(\frac{\sqrt{2}\left(x+1\right)}{\sqrt{x^2+2x+4}}\right)\right)+C

= π 2 2 1 2 cot 1 ( 2 ( x + 1 ) x 2 + 2 x + 4 ) + C \large \displaystyle = \frac{\pi }{2\sqrt{2}}-\frac{1}{\sqrt{2}}\cot ^{-1}\left(\frac{\sqrt{2}\left(x+1\right)}{\sqrt{x^2+2x+4}}\right)+C

= π 2 2 1 2 tan 1 ( 1 x + 1 x 2 + 2 x + 4 2 ) + C \large \displaystyle = \frac{\pi }{2\sqrt{2}}-\frac{1}{\sqrt{2}}\tan ^{-1}\left(\frac{1}{x+1}\sqrt{\frac{x^2+2x+4}{2}}\right)+C

= 1 2 tan 1 ( 1 x + 1 x 2 + 2 x + 4 2 ) + C + π 2 2 \large \displaystyle = -\frac{1}{\sqrt{2}}\tan ^{-1}\left(\frac{1}{x+1}\sqrt{\frac{x^2+2x+4}{2}}\right) + \boxed{C + \frac{\pi }{2\sqrt{2}}}

= 1 2 tan 1 ( 1 x + 1 x 2 + 2 x + 4 2 ) + C \large \displaystyle = -\frac{1}{\sqrt{2}}\tan ^{-1}\left(\frac{1}{x+1}\sqrt{\frac{x^2+2x+4}{2}}\right) + C'

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...